2020
DOI: 10.1101/2020.10.05.20205872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 RNA detection using pooling of self-collected samples: Simple protocol may foster asymptomatic surveillance

Abstract: Background: Surveillance of COVID infection and isolation of infected individuals is one of the available tools to control the spread of SAR-CoV-2. Asymptomatic and pre symptomatic are responsible for substantial transmission. RNA or antigen tests are necessary to identify non-symptomatic individuals. We tested the feasibility of using samples pooling offering different collection alternatives (swab/throat wash/saliva) to volunteers of a public health institute. Methods: We evaluated pool samples from both re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…The cycle threshold value was considered as an indicator of amplification. Although, the cycle threshold value (Ct) <37 as positive and Ct >37 as negative was proposed by the manufacturer in product information leaflet but in pooling approach, the Ct value is found to be higher with pooled samples corresponding to deconvoluted samples (Lopez-Lopes et al, 2020;Sami et al, 2021). Sami et al found a mean difference of 0.96 in cycle threshold (Ct) of pooled and deconvoluted positive samples (Sami et al, 2021).…”
Section: Results Of Rt-pcrmentioning
confidence: 99%
“…The cycle threshold value was considered as an indicator of amplification. Although, the cycle threshold value (Ct) <37 as positive and Ct >37 as negative was proposed by the manufacturer in product information leaflet but in pooling approach, the Ct value is found to be higher with pooled samples corresponding to deconvoluted samples (Lopez-Lopes et al, 2020;Sami et al, 2021). Sami et al found a mean difference of 0.96 in cycle threshold (Ct) of pooled and deconvoluted positive samples (Sami et al, 2021).…”
Section: Results Of Rt-pcrmentioning
confidence: 99%
“…Gargling a saline solution or filtered water can be carried out independently [38,39], saving the costs of support from clinical personnel and the accompanying personal protective equipment [39]. Moreover, gargle tests have been established as providing an effective approach to diagnosing respiratory infection among children [40], and they have been shown specifically to be effective in the diagnosis of SARS-CoV-2 infection [41]. The approach is particularly well-suited to a regular monitoring program, because samples from several participants can be tested together in a so-called pool testing procedure [41][42][43][44], with lower costs than individual testing [44].…”
Section: Testing Strategymentioning
confidence: 99%
“…Moreover, gargle tests have been established as providing an effective approach to diagnosing respiratory infection among children [40], and they have been shown specifically to be effective in the diagnosis of SARS-CoV-2 infection [41]. The approach is particularly well-suited to a regular monitoring program, because samples from several participants can be tested together in a so-called pool testing procedure [41][42][43][44], with lower costs than individual testing [44]. The possibility has been raised that pooling material prior to testing could potentially result in a reduced test sensitivity [44].…”
Section: Testing Strategymentioning
confidence: 99%
“…Further, pooled testing reduces the effort for participants, making it easier to monitor over extended periods of time. Pooling has been reported for PCR tests detecting SARS-CoV-2 [ 13 , 14 , 15 , 16 ]. A recent report from a company suggests that pooled samples can successfully be analyzed by lateral flow point of care (PoC) test cassettes [ 17 ], but pooling has not become an established practice for rapid antigen tests.…”
Section: Introductionmentioning
confidence: 99%